2011
DOI: 10.1002/pi.3156
|View full text |Cite
|
Sign up to set email alerts
|

Flexible polybenzoxazine thermosets containing pendent aliphatic chains

Abstract: The rich chemistry of polybenzoxazines allows a wide range of molecular structure design by using appropriate starting materials. A new class of polybenzoxazines has been developed from benzoxazine monomers containing pendent long aliphatic chains. The monomers have been synthesized by the reaction of phenol or bisphenol A with two different long-chain aliphatic amines. The chemical structure of the monomers was confirmed by 1 H nuclear magnetic resonance and Fourier transform infrared spectroscopy. The polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Fig. They found that the T g s of the resulting polybenzoxazines were in a range from 66 C to 101 C. 30,31 Agag et al reported that T g s of the polybenzoxazines containing pendent aliphatic chains were in a range from 81 C to 92 C. 32 Interestingly, the result of tan d curves showed that T g s of PCBB and PCBF were 94 C and 121 C, respectively (Fig. In general, a exible polybenzoxazine shows a low T g due to the poor thermal stability.…”
Section: Mechanical Properties Of the Biobased Polybenzoxazinesmentioning
confidence: 97%
See 1 more Smart Citation
“…Fig. They found that the T g s of the resulting polybenzoxazines were in a range from 66 C to 101 C. 30,31 Agag et al reported that T g s of the polybenzoxazines containing pendent aliphatic chains were in a range from 81 C to 92 C. 32 Interestingly, the result of tan d curves showed that T g s of PCBB and PCBF were 94 C and 121 C, respectively (Fig. In general, a exible polybenzoxazine shows a low T g due to the poor thermal stability.…”
Section: Mechanical Properties Of the Biobased Polybenzoxazinesmentioning
confidence: 97%
“…In general, a exible polybenzoxazine shows a low T g due to the poor thermal stability. 16,[30][31][32] In order to better understand the above phenomenon, crosslink density r(E 0 ) can be estimated from the rubbery plateau storage modulus at T g + 40 C according to the theory of rubbery elasticity (eqn (2)) as follows: [33][34][35][36] They found that the T g s of the resulting polybenzoxazines were in a range from 66 C to 101 C. 30,31 Agag et al reported that T g s of the polybenzoxazines containing pendent aliphatic chains were in a range from 81 C to 92 C. 32 Interestingly, the result of tan d curves showed that T g s of PCBB and PCBF were 94 C and 121 C, respectively (Fig.…”
Section: Mechanical Properties Of the Biobased Polybenzoxazinesmentioning
confidence: 99%
“…polyurethane [10,11] and polysiloxane [12]) into its thermosetting matrix to form a phase-separated morphology. Alternatively, the design of inherently tough polybenzoxazines by preparing benzoxazine monomers [13][14][15] or preferably prepolymers containing flexible segments has also been proposed. Thus, developing thermally curable polymeric precursors with benzoxazine units either as side chain [16] or as chain-end [17][18][19][20] or in main chain [21][22][23][24][25][26][27][28][29] some properties that are the combination of thermoplastic and thermosetting polymers such as processability, flexibility, high crosslinking density after cure, reductions in the vapor pressure during process and fragility for cured-structures are transferred to the cured resin.…”
Section: Scheme 1 Classical Benzoxazine Monomer Synthesis and Thermamentioning
confidence: 99%
“…A numerous studies have been conducted aiming to improve the toughness of the polybenzoxazine thermosets. The first one is related to the preparation of novel benzoxazine monomers containing aliphatic soft segments which can afford much tougher polybenzoxazines [22][23][24]. The second one is based on the incorporation of some elastomeric or thermoplastic polymers into the polybenzoxazine structure such as the use of rubber [25], polyurethane [26], polysiloxane [27], polysulfone [28], and poly(epsilon-caprolactone) [29] as the toughening agent blending with benzoxazine monomers.…”
Section: Introductionmentioning
confidence: 99%